2010
DOI: 10.1190/1.3481362
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for dense spatial sampling of multicomponent recording of converted waves in shallow marine environments

Abstract: A widespread use of converted waves for shallow marine applications is hampered by spatial aliasing and field efficiency. Their short wavelengths require dense spatial sampling which often needs to be achieved by receivers deployed on the seabed. We adopted a new methodology where the dense spatial sampling is achieved in the common-receiver domain by reducing the shot spacing. This is done by shooting one track multiple times and merging the shot lines in an effective manner in a separate processing step. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…() and some limited mode‐converted wave analysis (Bohlen et al . ; Allouche, Drijkoningen and van der Neut ; Allouche et al . ; Drijkoningen et al .…”
Section: Characterization Of Sedimentsunclassified
See 1 more Smart Citation
“…() and some limited mode‐converted wave analysis (Bohlen et al . ; Allouche, Drijkoningen and van der Neut ; Allouche et al . ; Drijkoningen et al .…”
Section: Characterization Of Sedimentsunclassified
“…Over the following sections, each of these parameters is considered in turn using a range of different example datasets However, a major limitation with the quantitative methods applied to the marine shallow subsurface is that S-waves or surface waves are only rarely considered. Notable exceptions are the multi-model surface wave inversion work of Socco et al (2011) and Vanneste et al (2011) and some limited mode-converted wave analysis (Bohlen et al 2004;Allouche, Drijkoningen and van der Neut 2010;Allouche et al 2011;Drijkoningen et al 2012). As S-waves are transmitted through the grain skeleton, they provide a more direct link between the geotechnical and geomechanical parameters than P-waves.…”
Section: Stress Regimementioning
confidence: 99%
“…This had been observed on the OBC as well (Allouche et al, 2010), which was initially interpreted as bad coupling, but the borehole sensors are well-coupled to the borehole wall, so the noise was therefore interpreted as generated by the river flow (∼3 m∕s). The main arrivals are the direct P-waves with a velocity of ∼1600 m∕s and the Scholte-wave with a velocity of 240 m∕s.…”
Section: Borehole Datamentioning
confidence: 99%
“…Recently, Allouche et al (2010Allouche et al ( , 2011 have shown that these nongeometrically converted shear waves are clearly observable in data from a marine environment. They used data from water-bottom receivers in a shallow canal to demonstrate this statement, and they modeled seismic data to verify whether the observed response was consistent with the simulated response.…”
Section: Introductionmentioning
confidence: 99%